POTENSI TANAMAN KIRINYUH (Chromolaena odorata L) DALAM MEREMEMEDIASI TANAH TERCEMAR MERKURI - Abraham Mariwy; Finarti Finarti; Sunarti Sunarti (Molluca Journal of Chemistry Education (MJoCE), 2022)
Research on the potential of the kirinyuh plant (Chromolaena odorata L.) in remediing mercury has been conducted. The kirinyuh plant is in a reactor that is powered by a 10 ppm mercury solution and is made with a variety of harvesting times of one, two, and three weeks. Mercury content analysis using mercury analyzer instrument ability of mercury accumulation and translocation in kirunyuh plant is determined from the value of BCF and TF.The results of the analysis showed mercury content in the plant kirinyuh reactor one on the soil, roots and leaves respectively: 0.70 ppm, 0.03463 ppm and 0.03595 ppm. In the second reactor is 1.89 ppm, 0.18 ppm and 1.45 ppm. For the third reactor is 9.63 ppm, 11.34 ppm and 10.95 ppm. While in the control reactor for soil samples is not detected, at the root of 0.20 ppm and on the leaves is 0.78 ppm. The BCF value of the kirinyuh plant in reactor one is 0.100828, in reactor two the BCF value is 0.862434 and in reactor three the BCF value is 2.3146. Tf values on reactor one, reactor two and reactor three in a row were 1.038117; 8.06 and 0.96560. the results of calculation of BCF and TF values show that kirinyuh plants tend to absorb and accumulate heavy metals, especially at the roots and headers so that this plant has accumulator properties or can absorb mercury so that it can be used as a phytoremediation agent of mercury-contaminated soil